2009
DOI: 10.1002/qj.446
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour variability induced by urban/rural surface heterogeneities during convective conditions

Abstract: Scientific interest in urban meteorology has increased because highly populated areas experience high vulnerability to pollution or heavy rain. However, compared to urban air quality or urban heat island (UHI) processes, the urban water vapour cycle is poorly understood because it has been investigated less due to the lack of upper-air measurements and the high sensitivity of surface measurements to local heterogeneities. In this paper, surface measurements of wind, temperature, pressure and humidity, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…This behaviour is systematic whatever the simulation day and is In addition to these limits, our scale truncation into large and small scales leads to an estimation of q r ls / q ref ls on a small number of points in the spectral domain, and probably a significant increase of the domain size (which however leads to a significant increase of the numerical cost) would have made more accurate the estimation of q r ls / q ref ls (Seth and Giorgi, 1998 (13), we obtain τ opt 3.4 h, which is close to the value obtained from the direct estimation (∼ 6 h) and to the value chosen in many numerical studies which generally justify this choice by the time interval between consecutive analyzes or reanalyses used to drive the RCM (e.g. Salameh et al, 2007;Champollion et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…This behaviour is systematic whatever the simulation day and is In addition to these limits, our scale truncation into large and small scales leads to an estimation of q r ls / q ref ls on a small number of points in the spectral domain, and probably a significant increase of the domain size (which however leads to a significant increase of the numerical cost) would have made more accurate the estimation of q r ls / q ref ls (Seth and Giorgi, 1998 (13), we obtain τ opt 3.4 h, which is close to the value obtained from the direct estimation (∼ 6 h) and to the value chosen in many numerical studies which generally justify this choice by the time interval between consecutive analyzes or reanalyses used to drive the RCM (e.g. Salameh et al, 2007;Champollion et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Understanding of urban land surface processes, such as transport of energy, water, trace gases and pollutants, is key to solving many urban environmental problems. In addition, accurate parametrizations of urban surface exchange schemes can substantially improve the performance of mesoscale numerical models (Cuenca et al, 1996;Masson, 2006;Champollion et al, 2009;Hamdi et al, 2010;Flagg and Taylor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At smaller scales, many studies have shown that landuse practices such as deforestation or changes due to agricultural management as well as urbanization may affect regional climate, ecosystems and water resources (Segal et al, 1988;Stohlgren et al, 1998;Pielke and Avissar, 1990;Lemonsu and Masson, 2002;Lemonsu et al, 2006; LINEAR BREEZE SCALING 1767 Champollion et al, 2009) and, on a global scale, spatially heterogeneous land-use effects may be at least as important in altering the weather as changes in climate patterns associated with greenhouse gases (Pielke et al, 2002;Pielke, 2005). Surface heterogeneities over the continent induce spatial variability in surface heat fluxes that can create inland breezes similar to sea/land breeze systems (Mahfouf et al, 1987;Mahrt et al, 1994;Patton et al, 2005;Courault et al, 2007).…”
Section: Introductionmentioning
confidence: 99%